"God's Ineffable Wounded Darkness". (3rd April 2018) - Odorisio, David M.
ABSTRACT: Dennis P. Slattery's A Pilgrimage Beyond Belief highlights the author's healing journey from childhood and adolescent trauma through explorations of Christian and Buddhist monasteries and retreat centers, including reflections on key writings from within each tradition.